Maternal Talk in Cognitive Development: Relations between Psychological Lexicon, Semantic Development, Empathy, and Temperament - Rollo, Dolores; Sulla, Francesco (Frontiers in Psychology, 2016)
In this study, we investigated the relationship between mothers’ psychological lexicon and children’s cognitive and socio-emotive development as assessed through conceptual and semantic understanding tasks, in addition to the traditional tasks of theory of mind. Currently, there is considerable evidence to suggest that the frequency of mothers’ mental state words used in mother-child picture-book reading is linked with children’s theory of mind skills. Furthermore, mothers’ use of cognitive terms is more strongly related to children’s theory of mind performances than the mothers’ references to other mental states, such as desires or emotions (Rollo, Buttiglieri, 2009). Current literature has established that early maternal input is related to later child mental state understanding; however it has not yet clarified which maternal terms are most useful for the socio-emotional and cognitive development of the child, and which aspect of the cognitive development benefits from the mother-child interaction. The present study addresses this issue and focuses on the relationship between mothers’ mental state talk and children’s behavior in conceptual and semantic tasks, and in a theory of mind task. In this study fifty pairs consisting of mothers and their 3 to 6-year-old children participated in two sessions: (1) The mothers read a picture book to their children. To assess the maternal psychological lexicon, their narrative was codified according to the categories of mental state references used in literature: perceptual, emotional, volitional, cognitive, moral and communicative. (2) After a few days, the conceptual and semantic skills of the children (tasks of contextualization and classification, memory and definition of words) and their psychological lexicon were assessed. The results suggest close links between the frequency and variety of mothers’ mental state words and some semantic and conceptual skills of children.